A new approach in the treatment and prevention of traumatic reticulitis - Kürşat TURGUT; Abdullah BAŞOĞLU; Yılmaz KOÇ; Mahmut OK; Mehmet MADEN; Mustafa ARICAN (Eurasian Journal of Veterinary Sciences)
A total 7 healthy bulls was used for this study. 5 ferromagnetic na11s, 6-8 cm in length were given per orally to each bulls via a tube at the begining of the experiment. At the second day of the experiment, the magnet surrounded by a brass cage with plastic - covered stainless steel chain was introduced per orally after 6 hours of the starvation. The magnat Was allawed to stay for hour in the reticulum. The magnet was reapplied the fallawing day for one hour in each animals. The results of the study showed that the instrument could be used as an alternative preventi ve or therapeutic maasure to permanant magnats and magnetic probes.